ANALISIS USAHATANI KOPI ARABIKA RAKYAT DI DESA KAYUMAS KECAMATAN ARJASA KABUPATEN SITUBONDO - Dwi Gita Dian Prahara; Sulistyaningsih Sulistyaningsih (AGRIBIOS, 2023)
Kayumas Village, Arjasa District, Situbondo Regency is one of the centers for smallholder Arabica coffee plantations where almost all farmers grow Arabica coffee. However, due to several factors, the income earned by smallholder Arabica coffee farmers is not optimal. The aim of this research is to find out how much farmers' income is and what factors influence the income of Arabica coffee farmers. The data used comes from the identity of the respondent (sample) and a list of questions (questionnaire) given to the Mulya Jaya and Sejahtera farmer groups. The sample used in this research was 60 respondents. The method used to analyze this research is quantitative descriptive. This research uses analysis of income data and multiple linear regression. The results of the research show that the income of smallholder Arabica coffee farmers in Kayumas Village is profitable. Factors that influence the income of smallholder Arabica coffee farmers are labor costs and fertilizer costs.